Antarctica and supercontinent evolution: historical perspectives, recent advances and unresolved issues - Harley, S.; Fitzsimons, Ian; Zhao, Y. (Geological Society Publishing House, 2013)
The Antarctic rock record spans some 3.5 billion years of history, and has made important contributions to our understanding of how Earth's continents assemble and disperse through time. Correlations between Antarctica and other southern continents were critical to the concept of Gondwana, the Palaeozoic supercontinent used to support early arguments for continental drift, while evidence for Proterozoic connections between Antarctica and North America led to the ‘SWEAT’ configuration (linking SW USA to East Antarctica) for an early Neoproterozoic supercontinent known as Rodinia. Antarctica also contains relicts of an older Palaeo- to Mesoproterozoic supercontinent known as Nuna, along with several Archaean fragments that belonged to one or more ‘supercratons’ in Neoarchaean times. It thus seems likely that Antarctica contains remnants of most, if not all, of Earth's supercontinents, and Antarctic research continues to provide insights into their palaeogeography and geological evolution. One area of research is the latest Neoproterozoic–Mesozoic active margin of Gondwana, preserved in Antarctica as the Ross Orogen and a number of outboard terranes that now form West Antarctica. Major episodes of magmatism, deformation and metamorphism along this palaeo-Pacific margin at 590–500 and 300–230 Ma can be linked to reduced convergence along the internal collisional orogens that formed Gondwana and Pangaea, respectively; indicating that accretionary systems are sensitive to changes in the global plate tectonic budget. Other research has focused on Grenville-age (c. 1.0 Ga) and Pan-African (c. 0.5 Ga) metamorphism in the East Antarctic Craton.These global-scale events record the amalgamation of Rodinia and Gondwana, respectively. Three coastal segments of Grenville-age metamorphism in the Indian Ocean sector of Antarctica are each linked to the c. 1.0 Ga collision between older cratons but are separated by two regions of pervasive Pan-African metamorphism ascribed to Neoproterozoic ocean closure. The tectonic setting of these events is poorly constrained given the sparse exposure, deep erosion level and likelihood that younger metamorphic events have reactivated older structures. The projection of these orogens under the ice is also controversial, but it is likely that at least one of the Pan-African orogens links up with the Shackleton Range on the palaeo-Pacific margin of the craton. Sedimentary detritus and glacial erratics at the edge of the ice sheet provide evidence for the c. 1.0 and 0.5 Ga orogenesis in the continental interior, while geophysical data reveal prominent geological boundaries under the ice, but there are insufficient data to trace these features to exposed structures of known age. Until we can resolve the subglacial geometry and tectonic setting of the c. 0.5 and 1.0 Ga metamorphism, there will be no consensus on the configuration of Rodinia, or the size and shape of the continents that existed immediately before and after this supercontinent. Given this uncertainty, it is premature to speculate on the role of Antarctica in earlier supercontinents, but it is likely that Antarctica will continue to provide important constraints when our attention shifts to these earlier events.